Too Cool? Hip Fracture Care and Maintaining Body Temperature - James Arkley; Suhib Taher MUDr; Ján Dixon MBBS; Gemma Dietz-Collin BSc; Stacey Wales BSc, MSc; Faye Wilson MBBS, MSC; William Eardley MBChB, MSc, PGCert Med ED, DipSEM (UK&I), MD, FRCSEd (Tr&Orth) (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
Introduction: Patients with hip fractures can become cold during the perioperative period despite measures applied to maintain warmth. Poor temperature control is linked with increasing complications and poorer functional outcomes. There is generic evidence for the benefits of maintaining normothermia, however this is sparse where specifically concerning hip fracture. We provide the first comprehensive review in this population. Significance: Large studies have revealed dramatic impact on wound infection, transfusion rates, increased morbidity and mortality. With very few studies relating to hip fracture patients, this review aimed to capture an overview of available literature regarding hypothermia and its impact on outcomes. Results: Increased mortality, readmission rates and surgical site infections are all associated with poor temperature control. This is more profound, and more common, in older frail patients. Increasing age and lower BMI were recognized as demographic factors that increase risk of hypothermia, which was routinely identified within modern day practice despite the use of active warming. Conclusion: There is a gap in research related to fragility fractures and how hypothermia impacts outcomes. Inadvertent intraoperative hypothermia still occurs routinely, even when active warming and cotton blankets are applied. No studies documented temperature readings postoperatively once patients had been returned to the ward. This is a point in the timeline where patients could be hypothermic. More studies need to be performed relating to this area of surgery.